Evaluation of oxidative stress responses in human circulating blood cells after imatinib mesylate treatment - Implications to its mechanism of action - Goran Gajski; Marko Gerić; Ana-Marija Domijan; Ivana Golubović; Vera Garaj-Vrhovac (Elsevier, 2019)
Imatinib mesylate (IM) is the first developed protein kinase inhibitor and recently it has topped consumption rates among targeted and total anticancer drugs. Although there are indications that IM possesses cyto/genotoxic activities against normal non-target cells as well, there is a lack of information regarding the underlying mechanism involved in those actions. Therefore, we aimed to evaluate the response of human circulating blood cells towards oxidative stress after IM treatment (0.0001-10 µg/mL) in vitro. Based on the results, IM had an influence on all of the oxidative stress parameters tested. Lower concentrations of IM induced an increase of glutathione level, following its decrease at higher IM concentrations indicating impairment in oxidative stress defences. Concomitant to a glutathione decrease, an increase of malondialdehyde and protein carbonyls level was observed indicating oxidative damage of lipids and proteins. The observed effects overlapped with the observed formation of oxidative base damage detected by formamidopyrimidine-DNA glycosylase modified-comet assay indicating that IM managed to induce oxidative DNA damage. Our results provide novelty in their mechanistic approach to IM-induced toxicity in non-target cells and suggest that IM can affect blood cells and induce oxidative stress. Keywords: Imatinib mesylate, Human peripheral blood cells, Non-target cells, Oxidative stress, Oxidative DNA damage